Cybercrime Regulations In Indonesia - Haura Adietyana (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
In today's world, technology is getting better. Computers, AI, and robots are getting more advanced. It makes things easier for people. People can shop, bank, send emails, study, and more online. Some people use technology to commit crimes. Cyber crime includes unauthorized access to computer systems, illegal content, data forgery, cyber espionage, cyber sabotage, infringement of privacy, carding, phishing, defacing, and cyber talking.